Urgensitas Musyawarah dalam Penyelesaian Perkara bagi Hakim Pengadilan Agama: Perspektif Al-Qur’an - Syafruddin, A. Ummu Fauziyyah; Fikri, Mursyid; Basri, Halimah; Sohrah, Sohrah (Universitas Islam Negeri Alauddin Makassar, 2024)
Judges have an important role in making decisions in handling cases, therefore judges need time to deliberate before enacting a law and deciding on a case, therefore the number of judges consists of three people because of the concept of judicial deliberation which is carried out before deciding on a case. This research aims to provide clarity regarding the study of Al-Musyawarah in resolving cases for judges in Religious Courts from the perspective of Al-Qur’an interpretation. This research methodology uses a type of library research using the Tafsir Mawdhui (Thematic) approach. The results of the research shed more light on the universality of Islamic law which can penetrate the dimensions of time as the main basis for making decisions. It is hoped that this research will be able to provide significant benefits for readers and serve as a reminder that the concept of the Al-Qur’an perspective is always able to be present in resolving every case from time to time and it is also the author's hope that in the future the status of the rule of law and the majority of Muslims in Indonesia able to provide a progressive collaborative existence